MnSOD Gene Knockout Promotes Apoptosis in Triple-Negative Breast Cancer BT-549 Cells Through Survivin Inhibition and Caspase-3 and Caspase-9 Modulation - Ghanny, Niken Rahmah; Wanandi, Septelia Inawati; Arumsari, Sekar; Paramita, Rafika Indah; Syahrani, Resda Akhra; Putri, Putu Indah Paramita Adi (Makara Journal of Science, 2024)
Triple-negative breast cancer (TNBC) is the most aggressive breast cancer subtype characterized by the lack of estro-gen, progesterone, and human epidermal growth factor receptor 2 (HER2) receptors. TNBC cells are becoming more aggressive due to the high expression of manganese superoxide dismutase (MnSOD) antioxidants to suppress reactive oxygen species-induced apoptosis and promote oncogenic signaling. This study was aimed to evaluate the effects of MnSOD knockout (KO) on TNBC cell apoptosis by assessing the survivin, caspase-9, and caspase-3 expressions. BT-549 TNBC cells containing the clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9-edited MnSOD gene were used to evaluate the messenger RNA (mRNA) expressions of survivin using the RT-qPCR assay. The West-ern blot assay was used to measure protein expressions of survivin, caspase-9, and caspase-3. Interactions between MnSOD and apoptosis-related proteins were simulated using computational methods based on molecular docking analysis and protein−protein interaction network. This study revealed that MnSOD KO decreased the binding affinity between MnSOD and survivin, in line with the significant reduction of survivin mRNA and protein expressions whereas the protein expressions of caspase-9 and caspase-3 increased in MnSOD KO cells. Therefore, MnSOD plays a pivotal role in BT-549 cell apoptosis by modulating survivin, caspase-9, and caspase-3 gene expressions. This study provides insights into a novel therapeutic strategy to mitigate the aggressiveness of TNBC by disrupting MnSOD gene expression. Further studies should elaborate the MnSOD signaling pathways involving closely related apoptotic proteins.